Additive Impact of Interleukin 6 and Neuron Specific Enolase for Prognosis in Patients With Out-of-Hospital Cardiac Arrest – Experience From the HAnnover COoling REgistry - Akin, Muharrem; Sieweke, Jan-Thorben; Garcheva, Vera; Martinez, Carolina Sanchez; Adel, John; Plank, Pia; Zandian, Paris; Sühs, Kurt-Wolfram; Bauersachs, Johann; Schäfer, Andreas (Frontiers in Cardiovascular Medicine, 2022)
Background: Patients after out-of-hospital cardiac arrest (OHCA) are at increased risk for mortality and poor neurological outcome. We assessed the additive impact of interleukin 6 (IL-6) at admission to neuron-specific enolase (NSE) at day 3 for prognosis of 30-day mortality and long-term neurological outcome in OHCA patients. Methods: A total of 217 patients from the HAnnover COoling REgistry with return of spontaneous circulation (ROSC) after OHCA and IL-6 measurement immediately after admission during 2017-2020 were included to investigate the prognostic value and importance of IL-6 in addition to NSE obtained on day 3. Poor neurological outcome was defined by cerebral performance category (CPC) ≥3 after 6 months. Results: Patients with poor outcome showed higher IL-6 values (30-day mortality: 2224±524 ng/l vs 186±15 ng/l, p<0.001; CPC ≥3 at 6 months: 1440±331 ng/l vs 180±24 ng/l, p<0.001). IL-6 was an independent predictor of mortality (HR=1.013/ng/l; 95% CI 1.007-1.019; p<0.001) and poor neurological outcome (HR=1.004/ng/l; 95% CI 1.001-1.007; p=0.036). In ROC-analysis, AUC for IL-6 was 0.98 (95% CI 0.96-0.99) for mortality, but only 0.76 (95% CI 0.68-0.84) for poor neurological outcome. The determined cut-off value for IL-6 was 431 ng/l for mortality (NPV 89.2%). In patients with IL-6 >431 ng/l, the combination with NSE <46 µg/l optimally identified those individuals with potential for good neurological outcome (CPC≤2). Conclusion: Elevated IL-6 levels at admission after ROSC were closely associated with 30-day mortality. The combination of IL-6 and NSE provided clinically important additive information for predict poor neurological outcome at 6 months.